1997
DOI: 10.1523/jneurosci.17-10-03664.1997
|View full text |Cite
|
Sign up to set email alerts
|

Astrogliosis in the Neonatal and Adult Murine Brain Post-Trauma: Elevation of Inflammatory Cytokines and the Lack of Requirement for Endogenous Interferon-γ

Abstract: The relevance of astrogliosis remains controversial, especially with respect to the beneficial or detrimental influence of reactive astrocytes on CNS recovery. This dichotomy can be resolved if the mediators of astrogliosis are identified. We have measured the levels of transcripts encoding inflammatory cytokines in injury systems in which the presence or absence of astrogliosis could be produced selectively. A stab injury to the adult mouse brain using a piece of nitrocellulose (NC) membrane elicited a prompt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 88 publications
7
71
0
Order By: Relevance
“…From the investigations of numerous groups, it has become evident that an increase in the levels of proinflammatory cytokines is a normal and early feature of the CNS response to trauma (1)(2)(3). In particular, we have shown that IL-1 and TNF-␣ become significantly elevated within the CNS parenchyma by 3 h after a brain stab wound injury, and are localized to the lesion site (4).…”
mentioning
confidence: 70%
“…From the investigations of numerous groups, it has become evident that an increase in the levels of proinflammatory cytokines is a normal and early feature of the CNS response to trauma (1)(2)(3). In particular, we have shown that IL-1 and TNF-␣ become significantly elevated within the CNS parenchyma by 3 h after a brain stab wound injury, and are localized to the lesion site (4).…”
mentioning
confidence: 70%
“…In a rat model of transient focal ischemia expression of TNFa and IL-1b mRNA was detected as early 1 h and peaked at 3 and 6 h, respectively (Wang et al, 1995). The induction of TNFa and IL-1b have been shown to be induced early in other brain injuries, for example, in a stabwound injury model in adult mouse brain, elevation of IL-1b and TNFa mRNA were observed at 6 to 12 h after the injury (Rostworowski et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, elevation of INF-␥ has been found in the brain of animals with autoimmune disorders such as experimental allergic encephalomyelitis (42,43), suggesting that under these conditions microglia might communicate to each other via Cx43 gap junctions induced by TNF-␣ plus INF-␥. On the other hand, after acute trauma the brain levels of INF-␥ mRNA remain unchanged, and in INF-␥ (Ϫ͞Ϫ) mice astrogliosis is still observed (44); thus, the inflammatory response after brain trauma may be mediated by a different set of cytokines. The fact that LPS or TNF-␣ plus INF-␥ did not induce dye coupling in every cultured microglial cell could be due to the known heterogeneity of microglia (45), the need for additional inflammatory mediators, and failure to use an appropriate concentration of the cytokines tested.…”
Section: Discussionmentioning
confidence: 99%